THE ANALYSIS OF INVESTMENT FEASIBILITY IN SHARE COMPANIESINSURANCE LISTED IN INDONESIA STOCK EXCHANGE (IDX) 2016-2018 - Dea Novita Sari; Febriyanto Febriyanto; Sri Retnaning Rahayu (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to analyze which stocks are efficient or feasible as an alternative to determine the best stock investment decision based on the Capital Asset Pricing Model (CAPM) Method. With this method, investors can estimate the expected rate of return at the risk of a stock. This research uses a descriptive method with a quantitative approach, the sample used is 11 shares from insurance subsector companies listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that the average systematic risk (beta) of 1.539 and Asuransi Jaya Tania Tbk (ASJT) has the highest beta. Of the total 11 companies that were sampled for the study there were 9 company shares that were eligible or efficient ie AHAP, AMAG, ASBI, ASJT, ASMI, ASRM, MREI, PNIN, VINS. and 2 company shares that were not feasible. These Stocks worth having an individual rate of return greater than the expected rate of return. While stocks are not feasible to have an individual rate of return smaller than the expected rate of return.Investors should buy this efficient shares and sell these inefficient shares.